The role of instructional scaffolding to facilitate problem-solving skills in improvisation / Farah Pauline Yong Abdullah - Farah Pauline, Yong Abdullah (2019)
The purpose of this study was to document and observe the role of instructional scaffolding process (ISP) to assist novice keyboard students at the initial stages of melodic improvisation. The study employed three action research cycles to identify the importance of instructional scaffolding through students learning outcome. The participants consisted of 8 beginner keyboard students (8 years old) from a public school. The duration for each action research cycle was twenty minutes and they were all conducted in the school’s music classroom. Three beginner keyboard pieces were introduced to students for the musical activities. The data collection procedure included the documentation and video-recorded lessons of the systematic instructional scaffolding process to facilitate problem-solving in melodic improvisation, and the students’ ability in creating own musical ideas in melodic improvisation. The instructional scaffolding processes for each research cycle were videotaped by two digital cameras for data analysis. The framework of the instructional scaffolding processes was guided from the book, The New Taxonomy of Educational Objectives, Marzano and Kendall (2007). The process of measuring students’ ability to problemsolve melodic improvisation was audio-recorded and their creation was written onto music scores in the third action research cycle.